Headache Rounds: Sudden, Transient Neurologic Symptoms in a Woman With Migraine. Issue 9 (October 2015) - Sharon, Roni; Rayhill, Melissa L.; Kurth, Tobias; Loder, Elizabeth
<x xml:space="preserve">Abstract</x> The following article is a Graham Headache Center headache rounds presentation at the Brigham and Women's Faulkner Hospital by fellows Roni Sharon and Melissa Rayhill with special guest Tobias Kurth. It summarizes the case of a 36‐year‐old female with no history of migraine in the past, presenting with several transient neurological episodes associated with headache. Her history, symptoms, imaging workup is reviewed. Following the case is a discussion of the differential diagnosis for the patient's symptoms along with a review of the association of migraine with and without aura with vascular neurological insult such as stroke. The article also discusses the clinical implications of migraine as a risk factor for stroke along with possible treatment recommendations.